Awareness of local people environmental issue and young people’s interest in climate change in Surakarta City, Central Java, Indonesia - Hue, Nguyen Thi; Minh, Dang Van; Antriyandarti, Ernoiz (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The effects of climate change in the atmosphere are starting to appear. This is clear, not only that it impacts the natural world, but also human cultures. In Indonesia, according to the IPCC estimates, these impacts are expected to increase over the coming decades. The temperature will increase, the amount of rainfall will decline and the rise in the sea level will impact a variety of coastal areas. Extreme weather conditions are also becoming more and more common,triggering problems such as flooding and droughts. Such developments present a significant challenge to human existence, economic growth, and the natural environment on which humans rely primarily for their prosperity. Moreover, these changes affect different levels and in different ways in every society. Methods: This research would have a general context for potential forecasts of the field of focus on climatic factors and climate change. The purpose of this study is to assess adolescents and local people on how local people appreciate and care about climate change in the city of Surakarta. The effort should also be made to examine for the area the factors that render society's essential realms susceptible to severe weather events. Results: The goal of this is to explain at some level the causes that increase the susceptibility of the local community when subjected to different triggers, as the effectiveness of adaptation or mitigation approaches is subject to population dynamics along with other variables.